Diagnostic value of conventional tumor markers in young patients with pulmonary nodules. Issue 9 (23rd July 2021) - Xu, Lihuan; Su, Zhiming; Xie, Baosong
Abstract: Background: Lung cancer is one of the most common malignancies, and there is a trend of increasing incidence in young patients. The preoperative diagnosis of pulmonary nodules is mainly based on the combination of imaging and tumor markers. There is no relevant report on the diagnostic value of tumor markers in young pulmonary nodules. Our study was designed to explore the value of five tumor markers in young patients with pulmonary nodules. Methods: We reviewed the medical records of 390 young patients (age ≤45 years) with pulmonary nodules treated at two separate centers from January 1, 2015, to January 1, 2021. Malignant pulmonary nodules were confirmed in 318 patients, and the other 72 patients were diagnosed with benign pulmonary nodules. The gold standard for diagnosis of pulmonary nodules was surgical biopsy. The conventional serum biomarkers included cytokeratin 19 (CYFRA21‐1), pro‐gastrin‐releasing‐peptide (ProGRP), carcinoembryonic antigen (CEA), neuron‐specific enolase (NSE), and squamous cell carcinoma‐associated antigen (SCCA). The diagnostic values of five tumor markers were analyzed by receiver operating characteristic (ROC) curves. Results: There were no significant differences in the expression of five tumor markers between the groups ( p  > 0.05). Single tumor marker (CYFRA21‐1, ProGRP, CEA, NSE, and SCCA) showed a limited value in the diagnosis of malignant pulmonary nodules, with the AUC of 0.506, 0.503 0.532, 0.548, and 0.562, respectively. The AUC of the combined examination was only 0.502~0.596, which did not improve the diagnostic value. Conclusions: Five conventional tumor markers had a limited diagnostic value in young patients with pulmonary nodules. Abstract : Preoperative diagnosis of pulmonary nodules is mainly based on the combination of imaging and tumor markers. Our study found the expression of the five tumor markers (CYFRA21‐1, ProGRP, CEA, NSE, and SCCA) did not differ significantly in young patients with pulmonary nodules. The AUC of tumor markers did not exceed 0.600, whether it was a single tumor marker or a combination of tumor markers.